Effects of Nishyinda, black pepper and cinnamon extract as growth promoter in broilers (Bangladesh Veterinarian, 2013)
An extract of nishyinda (Vitex negundo) leaves, black pepper (Piper nigrum) and cinnamon (Cinnamomum verum) (polyherbal extract) were used as growth promoter in broilers. A total of 20 day-old broiler chicks were purchased and after seven days of acclimatization randomly divided into two equal groups. No vaccination schedule was practised and no antibiotics were added in rations. Group A served as control while group B was supplemented with polyherbal extract 1 mL/litre in drinking water. Weekly body weight gain up to six weeks was measured and blood tests were performed at 21 and 42 days. Polyherbal extract significantly (P